2002
DOI: 10.1080/09537100120104863
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of human platelets by gingipain-R from Porphyromonas gingivalis cells and membrane vesicles

Abstract: The hypothesis that there is an association between periodontitis and cardiovascular disease suggests new lines of research on the mechanism whereby oral bacteria might exert systemic effects. This study was conducted to ascertain and quantitate the effect of Porphyromonas gingivalis on human platelets in vitro. A second related objective was to purify and identify the aggregating vector. Aggregation was measured by platelet turbidometry and gingipain-R was purified from P. gingivalis membrane vesicles by Seph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 33 publications
1
29
0
3
Order By: Relevance
“…Previous reports have shown that MVs possess various virulent abilities (9,13,25,39,40,43,48), while our results indicate a new aspect of cellular function impairment by P. gingivalis MVs.…”
Section: Discussionsupporting
confidence: 63%
“…Previous reports have shown that MVs possess various virulent abilities (9,13,25,39,40,43,48), while our results indicate a new aspect of cellular function impairment by P. gingivalis MVs.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, MVs have been reported to possess various virulent abilities (9,13,21,39,41,47,51). We intend to conduct additional studies to elucidate the cellular functions impaired by invading MVs.…”
Section: Discussionmentioning
confidence: 99%
“…This commensal can colonize, invade and multiply within gingival epithelial cells, as well as penetrate into deeper epithelial cell layers, potentially releasing the whole organism and/or virulence factors into the bloodstream (reviewed by Yilmaz, 2008). In addition to its ability to cause disease in the oral cavity, there are data indicating a role in systemic disease, including its ability to invade vascular endothelial cells (Dorn et al, 2000(Dorn et al, , 2002Jandik et al, 2008) and to cause aggregation of platelets (Pham et al, 2002). For many pathogenic bacteria, surface polysaccharides play a key role in immune modulation and evasion (Comstock & Kasper, 2006).…”
Section: Introductionmentioning
confidence: 99%